Feeding of mint leaf as an alternative to antibiotics on performance of broiler (Asian-Australasian Journal of Food Safety and Security, 2023)
The investigation was carried out through an experiment to examine how various quantities of mint leaves affect the production performance, carcass characteristics, immune parameters, and caecal microbial load of commercial broiler. A total of 225 one-day-old chicks of “Lohman Meat (Indian River)” strain having 43.00±0.66 g average body weight was divided into five investigational groups with three replications of 15 chicks each. The treatments were T0= control (basal feed), T1=basal feed + antibiotic, T2=basal feed + 1.0% mint leaf, T3=basal feed + 1.5% mint leaf and T4=basal feed + 2.0% mint leaf. Weekly body weight, feed intake and FCR were recorded during the investigation stage and carcass characteristics, immune parameters and caecal microbial count were also studied after. The average live weight and body weight gain were notably increased in the 2.0% mint leaf treated group than the other groups. Significant improved FCR was perceived in birds fed with 2.0% mint leaf with basal diet. The results showed that, broilers feeding with 2.0% mint leaf have significant effects (P0.05) on dressing percentage, breast and drumstick. Significant (P0.05) lower amount of Escherichia coli and Salmonella counts than in the control group. This study concluded that, the addition of mint leaf resulted in improved growth performance, carcass yields, immunity and lower pathogenic microbes in broiler chickens. Therefore, the use of 2.0% of mint leaf in the diets of broilers has affirmative effects on their production performance and as an antibiotic alternative in broiler production can be recommended.Asian Australas. J. Food Saf. Secur. 2023, 7 (1), 10-19